100 INSULIN REGULATES GENE TRANSCRIPTION BY O-GLYCOSYLATION AND PHOSPHORYLATION OF Sp1. (1st January 2005) - Harrington, A.; Majumdar, G.; Martinez-Hernandez, A.; Raghow, R.; Solomon, S.
Abstract : Insulin (INS) stimulates steady state levels of Sp1 transcription factor, which leads to increased calmodulin (CaM) gene expression. We have investigated the mechanism(s) involved and find that INS stimulates O-glycosylation (O-GlcNAc) of Sp1 as an obligatory precursor event. O-GlcNAcation-, followed by phosphorylation (PO4) of Sp1, regulates both its intracellular mobility and activity. To elucidate the mechanistic basis of these post-translational changes of Sp1 in response to insulin, we assessed temporal dynamics of accumulation of total, O-GlcNAc-modified and phosphorylated-Sp1 in H-411E liver cells exposed to 10, 000 μU/mL of insulin. Extracts from untreated and timed insulin treated cells were analyzed by Western blotting (Wb) using specific antibodies. The steady state levels of total and modified Sp1 were also investigated by confocal microscopy of H411E cells probed with Sp1-, O-GlcNAc-, and phosphoserine-specific antibodies that were detected with secondary antibodies labeled with various fluorochromes. The results from both Wb and confocal microscopy demonstrate that: INS stimulates (1) Sp1; (2) O-glycosylation of Sp1 early (30 min), which declines by 4 hours; and (3) phosphorylation of Sp1 in a steady increase through 4 hours. STZ, which inhibits O-GlcNAcase, and leaves Sp1 O-glycosylated, not only lead to intensified nuclear staining for O-GlcNAc-Sp1 but inhibited the insulin-driven expected nuclear staining for phosphorylated Sp1. Thus, reciprocal changes in O-GlcNAcation and phosphorylation of Sp1 in response to insulin appear to fine-tune calmodulin gene expression.